Concurrent product development process, project, and performance of Malaysian car manufacturer - Boejang, Hambali (2019)
New product development (NPD) has become more challenging with the increase in demand fluctuation, and technology advancement to cater to quality product performance, product customization and shorter lead time expectation. Thus, it is a norm for a manufacturer to establish its own formal NPD for these reasons. With concurrent engineering (CE), the manufacturer creates an enabling environment for effective and efficient NPD. The minor manufacturers are believed to have a different strategy of NPD from the major players in the automotive industry due to a limited pool of resources, and the target market. As such, the purpose of this study is to explore the NPD process and project of PROTON Sdn Bhd (PROTON) that is scant. Further, to have optimum NPD performance, the players in the automotive industry must overcome the moderate effect of project characteristics. For this, an investigation is done to identify how the formal NPD of PROTON mitigates the project characteristics. This study also considers the development of a measuring tool for NPD performance. Finally, analyses are carried out to verify the effect of formal NPD, CE best practices, co-development, and project characteristics on two NPD project goals: development time and cost. The findings obtained from scholarly articles enable the questionnaires for semi-structured personal and group interviews to be developed. Prior to the interviews, the questionnaires were pre-tested to confirm the intention of the questions being asked and avoid ambiguity. The findings from both interviews allow for the NPD process and project of PROTON to be outlined and defined. Besides, some variables were introduced and investigated through a survey, involving voluntary respondents. The investigation includes non-parametric statistical analyses in which the descriptive statistical analysis was used to investigate the influence of the selected variables on both project goals. Meanwhile, the associations between variables and their impact on the project goals were also investigated using inferential statistical analysis. The findings indicate that generally, the NPD process of PROTON is not that much different from the established NPD of other manufacturers in terms of the main development phases and tasks where the development tasks are executed in parallel by many related functions. As for the NPD project, there are five types of development projects that are normally done by PROTON. It is found that PROTON refers to the project characteristics based on the change contents of the vehicle and power train. In the meantime, the NPD performance matrix was successfully developed and tested through a feasibility study. It was named “Boejang Performance Matrix” (BPM) and enables the management to make a decision on specific NPD project performance. The effect of those selected variables on, and their association with the project goals are found to be according to the existing theories, except for the incremental innovation as for PROTON of which the research and development (R&D) capability is weak, the incremental innovation is actually not a significant threat to the project performance. Therefore, a formal NPD is crucial for both minor and major car manufacturers, and it helps to reduce the negative effects of project characteristics for optimum NPD performance and product success.